THE INFLUENCE OF WORK ENVIRONMENT AND GIVING REWARDS ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT. SUKA MELAJU - Nadilla, Nia; Diana, Yusvi; Karlinda, AI Elis; Lusiana, Lusiana (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTThis study aims to determine the effect of the work environment and reward on employee performance through job satisfaction as an intervening variable at PT. Suka Melaju. The sample in this study was taken using the saturated sample method. The number of samples used were 76 people. The analytical method used is Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS). To test the hypothesis, the Path Coefficient is used, namely the test carried out to see the direct effect and the Indirect Effect, which is a test that aims to see the indirect effect. The results of this study indicate that: 1) The work environment has a positive and insignificant effect on job satisfaction at PT. Suka Melaju 2) giving rewards has a positive and significant effect on job satisfaction at PT. Suka Melaju. 3) The work environment has a positive and significant effect on employee performance at PT. Suka Melaju. 4) Giving rewards has a negative and insignificant effect on the performance of employees at PT. Suka Melaju. 5) Job satisfaction has a positive and significant effect on employee performance at PT. Suka Melaju 6) Job Satisfaction mediates the influence of the work environment on employee performance at PT. Suka Melaju 7) Job Satisfaction does not mediate the effect of giving rewards to employees at PT. Suka Melaju.Keywords: work environment, giving rewards, employee performance, job satisfaction.